Mebendazole inhibits tumor growth and prevents lung metastasis in models of advanced thyroid cancer. Issue 3 (March 2020) - Williamson, Tara; Mendes, Thais Biude; Joe, Natalie; Cerutti, Janete M; Riggins, Gregory J
Abstract : The most common thyroid malignancy is papillary thyroid cancer. While a majority respond to therapy and have a favorable prognosis, some papillary thyroid cancers persist. This subset may dedifferentiate to anaplastic thyroid cancer, an aggressive, highly invasive and rapidly fatal cancer. Thyroid cancer patients at risk for disease progression and metastasis need earlier, safer and more effective therapies. The purpose of this translational study was to determine if mebendazole could be repurposed to effectively treat thyroid cancer, in particular before metastasis. In vitro, mebendazole potently inhibited the growth of a panel of human papillary and anaplastic thyroid cancer cells. In papillary (B-CPAP) and anaplastic (8505c) cell lines, mebendazole increased the percentage of cells in G2/M cell cycle arrest and induced late stage apoptosis by activation of the caspase-3 pathway. In aggressive 8505c cells, mebendazole significantly repressed migratory and invasive potential in a wound healing and transwell invasion assay and inhibited expression of phosphorylated Akt and Stat3 and reduced Gli1. In vivo, mebendazole treatment resulted in significant orthotopic thyroid tumor regression (B-CPAP) and growth arrest (8505c), with treated tumors displaying reduced expression of the proliferation maker KI67 and less vascular epithelium as indicated by CD31+ immunohistochemistry. Most importantly, daily oral mebendazole prevented established thyroid tumors from metastasizing to the lung. Given the low toxicity and published anticancer mechanisms of mebendazole, this novel preclinical study of mebendazole in thyroid cancer has promising therapeutic implications for patients with treatment refractory papillary or anaplastic thyroid cancer.